(3GdfXGe GdbGfhfj ddGSJKeGQ GdCLfHj aj GdeedcI GdYQHjI GdSYhOjI (B/s - (3eQSj, eMeO eUWai YHO GdUGObs ((3GdefUhQI (B[(3eUQ(B] :s (3OGQ GdacQ hGdbGfhf,s, 2022)
(3JJLGhR gPg GdOQGSI MJeG GdJbfjf GdeYQha HGSe (B%22(3fRGe GSJKeGQ QGS GdeGd GdCLfHj(B%22 (3dJTed GdbhGYO GdeJUdI HgPG GdGSJKeGQ LejYgG CjG cGf eUOQgG GdfXGej(B. (3hjecf dgPg GdOQGSI Cf JMbb HGdEVGaI Edi eG JbOe aDGFO YOjOI JYhO Ydi eNJda CWQGa YedjI GdGSJKeGQ GdPi jJe aj Ebdje GdeecdI, MjK SJSGYO Ydi GSJLdGA eG jchf bO GYJQi fUhU GdCfXeI GdeYfjI ef ZehV hQaY eG HjfgG ef JYGQV hGSJceGd eG ajgG ef fbU, dfgG fUhU JfJei dCfXeI eNJdaI hVYJ aj efGSHGJ hJhGQjN eJZGjQI(B. (3hSJSGYO gPg GdOQGSI Ydi JHSjW age gPg GdfUhU haj cd eG JbOe aGFOI eMbbI ddehXa GdbGFe Ydi JWHjb gPg GdCfXeI, dCfgG OQGSI JLYd dg hHjf jOjg fUhUG WjYI hGVMI GdeYGfjI hGdeYGde hGdMOhO(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdGSJKeGQs -- (3EOGQIs; (3GdGSJKeGQGJ GdCLfHjIs -- (3bhGfjf hJTQjYGJs -- (3GdSYhOjIs